A complex case of necrotizing pneumonia and parapneumonic effusion in a healthy 20-month-old child: Successful management with video-assisted thoracoscopic surgery and chest tube placement - Thuy-Ngan Nguyen-Thi, MD; Khoa Nguyen-Dang, MD; Hanh-Duyen Bui-Thi, MD; Minh-Hong Pham-Thi, MD, PhD (Radiology Case Reports, 2024)
Necrotizing pneumonia (NP) is characterized by destruction of pulmonary tissue, resulting in multiple thin-walled cavities. There are limited reports on NP and parapneumonic effusion cases in children associated with Pseudomonas aeruginosa. Currently, there is no consensus regarding the optimal timing for video-assisted thoracoscopic surgery (VATS) following failure of chest tube placement and antibiotic treatment. A healthy 20-month-old child was hospitalized with symptoms of community-acquired pneumonia, progressing to severe NP and parapneumonic effusion. Despite receiving broad-spectrum antibiotics and chest tube placement on the third day of treatment, the condition continued to deteriorate, prompting VATS intervention on the sixth day. The presence of a “split pleural sign“ and extensive lung necrosis on chest computed tomography contributed to initial treatment failure. Multidrug resistance P. aeruginosa was identified through nasal trachea aspiration specimens on the eighth day of treatment, leading to an adjustment in antibiotic therapy to high-dose meropenem and amikacin. Subsequently, the patient became afebrile, showed clinical improvement, and was discharged after 35 days of treatment. Through this case, we aim to emphasize an unusual pathogenic bacteria in the context of NP and the need for standardized surgical interventions in pediatric patients with NP.